Implementing care-related services in care units - an interview study - Dorothea Reichert; Karl Gummesson; Lars Wallin; Tobias Dahlström (BMC, 2024)
Abstract Background The growing concern about a dwindling healthcare workforce, exacerbated by demographic changes, calls for innovative solutions. One viable approach involves implementing new professional roles and restructuring existing healthcare teams within hospital care units. Objectives To evaluate the implementation of an innovative task-shifting concept, care-related services (CRS), from the managers' perspective in somatic care units across the hospitals in a region in Sweden. Methods The qualitative study was conducted in 2022, after the implementation of CRS. Individual interviews were conducted with 24 key stakeholders, including 14 care unit managers, six CRS managers, and four process managers. A qualitative content analysis was performed, utilizing the Consolidated Framework of Implementation Research (CFIR). Results The implementation of CRS involved collaboration between care unit managers, CRS managers, and project managers, alongside CRS staff, registered nurses (RNs), and licensed vocational nurses (LVNs). In particular, their roles encompassed defining boundaries, establishing routines, and managing personnel. Throughout the implementation process, challenges emerged, stemming from undefined goals, difficulties in recruiting qualified CRS staff, and issues associated with seamlessly integrating CRS into existing work routines. These challenges arose due to a constrained timeframe, widespread team apprehension, shortcomings in the training of CRS staff, unclear task allocation, and an increased workload for care unit managers. Factors associated with successful CRS implementation included effective cooperation among managers and an open-minded approach. Conclusions Our findings highlight the crucial role of clear communication, effective recruitment, integration of CRS staff, clarification of roles, responsibilities, and defined goals for successful CRS implementation.